Answer:
x = 36
Step-by-step explanation:
(3/4)*x-((2/3)*x)-4 = (1/6)*x-7 // - (1/6)*x-7
(3/4)*x-((2/3)*x)-((1/6)*x)-4+7 = 0
(3/4)*x+(-2/3)*x+(-1/6)*x-4+7 = 0
3-1/12*x = 0 // - 3
-1/12*x = -3 // : -1/12
x = -3/(-1/12)
x = 36
Answer:
20%
Step-by-step explanation:
Use the percent change formula: difference = % * original cost
12 - 10 = 2
The difference is 2 and the original cost is 10. Now, we have the equation
2 = % * 10. We don’t know the percentage right? So now we have to find the percentage. To do this, you will have to do 2 divided by 10, which is 0.20. Lastly, we have to turn 0.20 into a percentage by multiplying it by 100, leaving you with 20%. So therefore, 20% is the percent increase. Hope this helps!
Let
a1=1/40
a2=4/40
a3=9/40
a4=16/40
a5=25/40
a6=?
we know that
a2-a1=4/40-1/40----> 3/40
a3-a2=9/40-4/40-----> 5/40
a4-a3=16/40-9/40----> 7/40
a5-a4=25/40-16/40---> 9/40
the difference is
3/40,5/40,7/40.9/40,....
3/40+[2/40]---> 5/40
5/40+[2/40]---> 7/40
7/40+[2/40]---> 9/40
the next will be
9/40+[2/40]-----> 11/40
so
the next term is 25/40+[11/40]------> 36/40
the answer is
36/40